(untitled) (Advancements in Homeopathic Research, 2024)
Introduction: Serum anguillae, derived from eel serum, is a recent addition to the homoeopathic materia medica with notable efficacy in renal, cardiac, and hepatic conditions. Objective: This article provides an updated materia medica, integrating clinical observations, toxicological data, and pharmacological activities. Methodology:A systematic review of classical and contemporary sources was conducted to compile this materia medica. Results and Discussion: The remedy’s therapeutic potential is explored, aligning traditional homoeopathic uses with modern biomedical findings, offering insights into broader clinical applications. However, further reprovings can be considered to explore the depth of remedy action.